Phylogenomic Species Delimitation Dramatically Reduces Species Diversity in an Antarctic Adaptive Radiation. (10th July 2021) - Parker, Elyse; Dornburg, Alex; Struthers, Carl D; Jones, Christopher D; Near, Thomas J
Abstract: Application of genetic data to species delimitation often builds confidence in delimitations previously hypothesized using morphological, ecological, and geographic data and frequently yields recognition of previously undescribed cryptic diversity. However, a recent critique of genomic data-based species delimitation approaches is that they have the potential to conflate population structure with species diversity, resulting in taxonomic oversplitting. The need for an integrative approach to species delimitation, in which molecular, morphological, ecological, and geographic lines of evidence are evaluated together, is becoming increasingly apparent. Here, we integrate phylogenetic, population genetic, and coalescent analyses of genome-wide sequence data with investigation of variation in multiple morphological traits to delimit species within the Antarctic barbeled plunderfishes (Artedidraconidae: Pogonophryne ). Pogonophryne currently comprises 29 valid species, most of which are distinguished solely by variation in the ornamentation of the mental barbel that projects from the lower jaw, a structure previously shown to vary widely within a single species. However, our genomic and phenotypic analyses result in a dramatic reduction in the number of distinct species recognized within the clade, providing evidence to support the recognition of no more than six species. We propose to synonymize 24 of the currently recognized species with five species of Pogonophryne . We find genomic and phenotypic evidence for a new species of Pogonophryne from specimens collected in the Ross Sea. Our findings represent a rare example in which the application of molecular data provides evidence of taxonomic oversplitting on the basis of morphology, clearly demonstrating the utility of an integrative species delimitation framework.[ddRADseq; multispecies coalescent; Notothenioidei; SNPs; Southern Ocean.]